Programmatic implementation of the Dijkstra algorithm in the Transact-SQL language using relational algebra - Urubkin, Mikhail; Galushka, Vasiliy; Fathi, Vladimir; Fathi, Denis; Petrenkova, Sofya (E3S web of conferences, 2020)
The article is devoted to the topical issue of data processing in the database management systems. It presents a solution to the problem of finding paths in a graph using Dijkstra’s algorithm, set as a sequence of relational operations and functions of the Transact-SQL language. The efficiency of the known information system architectures and the impact of various ways of distributing functions between system components are reviewed. The article describes features of the relational algebra and the Transact-SQL operations, and provides a brief description of Dijkstra’s algorithm. For its programmatic implementation, several stages are defined, for each of which a formal description of the relational operations performed on it is given. The outputs of these operations are shown using the example of the database tables, and the algorithm to find the final path is given. The issues of the proposed method’s productivity and security of programmatic implementation of the path search in a graph are discussed separately.